Estudo microestrutural dos contornos de grão em estágio inicial de formação no sistema cerâmico ZnO-Bi2O3 - Martinho, Marcelo Antonio Donizetti (2019)
Polycrystalline materials have solid-solid interfaces known as grain boundary. These interfaces have long been treated as just a region of defects between the crystals (grains), but recent studies have shown that such interfaces have a major influence on material properties. With the advancement of technology, experimental and theoretical studies about grain boundaries have shown that such interfaces can have their own structures, called complexions, and phase changes among themselves, altering the properties and behavior of the material. Such studies lead to an objective that is to superimpose a phase diagram of grain boundary structures to a bulk phase diagram, which could provide a refined control of material properties by controlling composition, temperature and sintering conditions. However, the study of complexions is new and incomplete because there is not a large amount of studies on this phenomenon and one area developed for understanding grain boundaries is grain contour engineering. The study carried out in this work aimed at the visualization and understanding of the process of segregation in interface and the consequent formation of early stage complexions in the ZnO / Bi2O3 system, widely used in varistors. For this purpose, two processes were used: the preparation of samples with the selection of the work area with the focused ion beam (FIB) technique and the subsequent visualization of the grain outlines and their respective phenomena and structures by transmission electron microscopy (TEM), where it was possible to visualize grain boundary structures already described in the literature and to prove the more complex phase transitions between complexions and nucleation, including nucleation of complexions outside the interface.